(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
The article covers work to eliminate the problems of obtaining high-strength binders, i.e., important environmental defects and disadvantages of cements, the need to use large amounts of energy in their production, the release of large CO2 and dust emissions, environmental damage and their prevention.